Los Avatares De Las Acciones Gubernamentales Que Combaten El Acoso Escolar En El Estado De San Luis Potosí - González Torres María de Lourdes; Vega Campos Miguel Ángel; Mballa Louis Valentin (European Scientific Journal, ESJ, 2017)
The purpose of this article is to report the actions taken by the government in fighting against bullying in the State of San Luis Potosi. The study was carried out based on article 4° of the Mexican Constitution and article 12° of the San Luis Potosi Estate Constitution. Here, it was established that the State is responsible for the fulfillment of the best interest of the child and it must fully guarantee their rights. Also, these articles states that this principle shall guide the design, monitoring, and evaluation of public policies aimed at them. It is well known that bullying exist and is growing increasingly. For instance, this can be seen in 2000 and 2003 through the Child and Youth Consultations of the Federal Electoral Institute. In 2008, a study was conducted by the National Institute of Psychiatry. In 2009, the National Report on Gender Violence was carried out by the Secretariat of Public Education and the United Nations Fund. In 2012, the National Results of the Child and Youth Consultation was obtained. A study in 2014 exhorts the Federal Executive to carry out the necessary public policies in order to prevent and reduce bullying. In the same year, a special report was given on the aspect of respect for human rights in public secondary schools in the State of San Luis Potosí. In conclusion, despite knowing the problem of bullying, there is still no specific and concrete policy to fight bullying in San Luis Potosi.